2022
DOI: 10.1039/d2tb00174h
|View full text |Cite
|
Sign up to set email alerts
|

Porous dynamic covalent polymers as promising reversal agents for heparin anticoagulants

Abstract: Heparins are natural and partially degraded polyelectrolytes that consist of sulfated polysaccharide backbones. However, as clinically used anticoagulants, heparins are associated clinical bleeding risks and thus require rapid neutralization. Protamine...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 71 publications
0
2
0
Order By: Relevance
“…Multivalency has been established as an efficient strategy for this aim, as demonstrated by protamine, whose guanidine groups in the side chains multivalently form electrostatic binding with the anionic groups of heparins. We previously reported that polymeric frameworks formed by tri- and tetracationic precursors can adsorb both UFH and LMWHs to neutralize their anticoagulant action. , We thus designed and prepared a library of caltrop-like multicationic molecules TP-1–8 , TI-1 , TI-2 , and TQ-1 (Figure ), which consisted of pyridinium, imidazolium, or isoquinoline-2-ium units and discrete side chains bearing a peripheral amino group, to test their potential as small-molecule antidotes for heparin neutralization. All the compounds displayed good solubility in water.…”
Section: Resultsmentioning
confidence: 99%
“…Multivalency has been established as an efficient strategy for this aim, as demonstrated by protamine, whose guanidine groups in the side chains multivalently form electrostatic binding with the anionic groups of heparins. We previously reported that polymeric frameworks formed by tri- and tetracationic precursors can adsorb both UFH and LMWHs to neutralize their anticoagulant action. , We thus designed and prepared a library of caltrop-like multicationic molecules TP-1–8 , TI-1 , TI-2 , and TQ-1 (Figure ), which consisted of pyridinium, imidazolium, or isoquinoline-2-ium units and discrete side chains bearing a peripheral amino group, to test their potential as small-molecule antidotes for heparin neutralization. All the compounds displayed good solubility in water.…”
Section: Resultsmentioning
confidence: 99%
“…There are also cationic polymers such as universal heparin reversal agent, dynamic covalent polymers, and others described by Bromfield et al, which could be useful as neutralizers in diagnostic tests, although further research is needed to check if their efficacy profile could be better than protamine [121][122][123].…”
Section: Other Cationic Polymersmentioning
confidence: 99%